2018
DOI: 10.1186/s13063-018-2725-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of voluminous and complicated superficial slow-flow vascular malformations with sirolimus (PERFORMUS): protocol for a multicenter phase 2 trial with a randomized observational-phase design

Abstract: BackgroundSlow-flow superficial vascular malformations (VMs) are rare congenital anomalies that can be responsible for pain and functional impairment. Currently, we have no guidelines for their management, which can involve physical bandages, sclerotherapy, surgery, anti-inflammatory or anti-coagulation drugs or no treatment. The natural history is progressive and worsening. Mammalian target of rapamycin (mTOR) is a serine/threonine kinase that acts as a master switch in cell proliferation, apoptosis, metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The mTOR pathway is involved in various pathological mechanisms of lymphangiogenesis, lymphatic metastasis and several cancer developments, including colorectal cancer, gastric cancer, liver cancer, breast cancer and uterine cancer 15–17 . Sirolimus known as a mTOR inhibitor has an antiproliferative effect on lymphatic vessels, and is clinically used for a difficult‐to‐treat lymphatic anomalies 12,13,18–20 . Sirolimus binds the FK‐binding protein 12, resulting in a complex that prevents phosphorylation and activation of 4EBP1 and S6K1 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTOR pathway is involved in various pathological mechanisms of lymphangiogenesis, lymphatic metastasis and several cancer developments, including colorectal cancer, gastric cancer, liver cancer, breast cancer and uterine cancer 15–17 . Sirolimus known as a mTOR inhibitor has an antiproliferative effect on lymphatic vessels, and is clinically used for a difficult‐to‐treat lymphatic anomalies 12,13,18–20 . Sirolimus binds the FK‐binding protein 12, resulting in a complex that prevents phosphorylation and activation of 4EBP1 and S6K1 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR inhibitor sirolimus (also called rapamycin) is used for the treatment of unresectable and locally advanced lymphatic anomalies. Preclinical trials have been conducted to test the efficacy of mTOR inhibitor in lymphatic anomalies 12,13 . However, little is known about the expression of mTOR pathway components in lymphatic anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse malformations present significant challenges due to the morbidity of interventional treatments to achieve local control. There are currently no guidelines for treatment of LMs [3]. mTOR inhibitors, such as sirolimus, have recently been used for their antilymphangiogenic properties in treating LMs [4].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study demonstrated that PIK3CA mutation excessively promoted activation of mTOR pathway [ 7 , 13 ]. Moreover, sirolimus known as a mTOR inhibitor has an antiproliferative effect on various vascular anomalies including FAVA [ 3 , 14 , 15 ]. Considering these findings, activated PI3K/AKT/mTOR signaling pathway plays a key role in pathogenesis of vascular anomaly in FAVA.…”
Section: Introductionmentioning
confidence: 99%